2019
DOI: 10.1038/s41598-019-44192-5
|View full text |Cite
|
Sign up to set email alerts
|

Little evidence for switches to environmental sex determination and turnover of sex chromosomes in lacertid lizards

Abstract: Amniotes possess variability in sex determination, from environmental sex determination (ESD), where no sex chromosomes are present, to genotypic sex determination (GSD) with highly differentiated sex chromosomes. Some evolutionary scenarios postulate high stability of differentiated sex chromosomes and rare transitions from GSD to ESD. However, sex chromosome turnovers and two independent transitions from highly differentiated ZZ/ZW sex chromosomes to ESD were previously reported in the lacertid lizards. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 53 publications
(71 reference statements)
3
46
1
1
Order By: Relevance
“…Later, Rovatsos et al [2016Rovatsos et al [ , 2019c used transcriptome analysis and qPCR to identify hemizygous, and thus suggestively Z-linked, genes in several species of lacertids, including L. agilis from the Czech Republic ( L. agilis argus ). In these studies, the genes reported as Z-specific by Srikulnath et al [2014] were identified as (pseudo)autosomal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Rovatsos et al [2016Rovatsos et al [ , 2019c used transcriptome analysis and qPCR to identify hemizygous, and thus suggestively Z-linked, genes in several species of lacertids, including L. agilis from the Czech Republic ( L. agilis argus ). In these studies, the genes reported as Z-specific by Srikulnath et al [2014] were identified as (pseudo)autosomal.…”
mentioning
confidence: 99%
“…In these studies, the genes reported as Z-specific by Srikulnath et al [2014] were identified as (pseudo)autosomal. The orthologues of the Z-linked genes which were determined by Rovatsos et al [2016Rovatsos et al [ , 2019c are located in 2 microchromosomes of A. carolinensis , ACA11 and ACA16 (homologous to GGA4p and GGA17, respectively) [Kichigin et al, 2016]. Rovatsos et al suggested that the Z chromosome of lacertids should be one of the small macrochromosomes, formed via fusion of 2 ancestral squamate microchromosomes [Uno et al, 2012].…”
mentioning
confidence: 99%
“…3a). The absence of the signal on the W chromosome is apparently due to the fact that the W chromosome of lacertids is too degenerated and does not hybridize with the DNA from the Z chromosome [Rovatsos et al, 2019b; Andrade et al, 2019]. The autosomes were identified as pairs 13 and 14 basing on the position of the LST_L peak in the flow karyotype.…”
Section: Resultsmentioning
confidence: 99%
“…Later, Rovatsos et al [2016; 2019b] used transcriptome analysis and qPCR to identify hemizygous and thus suggestively Z-linked genes in several species of lacertids, including L. agilis from the Czech Republic ( L. agilis argus ). In these works, the genes identified by Srikulnath et al [2014] as Z-specific were identified as (pseudo)autosomal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation